Randomised controlled trial of topical kanuka honey for the treatment of acne. Issue 2 (1st February 2016) - Semprini, Alex; Braithwaite, Irene; Corin, Andrew; Sheahan, Davitt; Tofield, Christopher; Helm, Colin; Montgomery, Barney; Fingleton, James; Weatherall, Mark; Beasley, Richard
Abstract : Objective: To investigate the efficacy of Honevo, a topical 90% medical-grade kanuka honey, and 10% glycerine (honey product) as a treatment for facial acne. Design: Randomised controlled trial with single blind assessment of primary outcome variable. Setting: Outpatient primary care from 3 New Zealand localities. Participants: Of 136 participants aged between 16 and 40 years with a diagnosis of acne and baseline Investigator's Global Assessment (IGA) for acne score of ≥2.68, participants were randomised to each treatment arm. Interventions: All participants applied Protex, a triclocarban-based antibacterial soap twice daily for 12 weeks. Participants randomised to the honey product treatment arm applied this directly after washing off the antibacterial soap, twice daily for 12 weeks. Outcome measures: The primary outcome was ≥2 point decrease in IGA score from baseline at 12 weeks. Secondary outcomes included mean lesion counts and changes in subject-rated acne improvement and severity at weeks 4 and 12, and withdrawals for worsening acne. Results: 4/53 (7.6%) participants in the honey product group and 1/53 (1.9%) of participants in the control group had a ≥ 2 improvement in IGA score at week 12, compared with baseline, OR (95% CI) for improvement 4.2 (0.5 to 39.3), p=0.17. There were 15 and 14 participants who withdrew from the honey product group and control group, respectively. Conclusions: This randomised controlled trial did not find evidence that addition of medical-grade kanuka honey in combination with 10% glycerine to standard antibacterial soap treatment is more effective than the use of antibacterial soap alone in the treatment of acne. Trial registration number: ACTRN12614000003673; Results.